Identification of the pest outbreak in the coastal mangrove ecosystem of Mahakam Delta, East Kalimantan, Indonesia - HARMONIS HARMONIS; MUHAMMAD TAUFIQ HAQIQI; MUHAMMAD FIRDAUS AL FAHRONI; JEFRY JEFRY; SANTIKA GUNAWAN; MUHAMMAD AFIF SEKEDANG; DAVIS RAHMAT; NUR FARIZ AZHAR; MUHAMMAD OKY PRATAMA SEPTIAJI PUTRA; FITRIA DEWI KUSUMA; MARYA TIARA HAPSARI; FERNANDA ALVA MUHAMMAD; RITA DIANA; TRIYONO SUDARMADJI; RUDIANTO AMIRTA; ARIYANTO ARIYANTO; OSHLIFIN RUCMANA SAUD; FENNY PUTRI MARIANI SOFYAN; FAJRIANSYAH FAJRIANSYAH; AGUS MASHUD S. ASNGARI; YULIUS S. BULO; IKHSAN SALMAN; RIFKI RIZALDI; KHAIRUL MUKMIN LUBIS (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Harmonis, Haqiqi MT, Fahroni MFA, Jefry, Gunawan S, Sekedang MA, Rahmat D, Azhar NF, Putra MOPS, Kusuma FD, Hapsari MT, Muhammad FA, Diana R, Sudarmadji T, Amirta R, Ariyanto, Saud OR, Sofyan FPM, Fajriansyah, Asngari AMS, Bulo YS, Salman I, Rizaldi R, Lubis KM. 2024. Identification of the pest outbreak in the coastal mangrove ecosystem of Mahakam Delta, East Kalimantan, Indonesia. Biodiversitas 25: 829-835. Mangrove ecosystems are considered the most essential areas in the wetland since they sequester carbon more efficiently than terrestrial ecosystems. Thus, they have received significant attention as a nature-based solution to achieve the Naturally Determined Contributions in the commitment to global climate change mitigation. Currently, the degradation of mangroves has been linked to serious threats, including pest outbreaks. Our primary objective was to assess the pest outbreaks that occurred in the coastal mangroves of the Mahakam Delta, Indonesia. This study was conducted in two areas in Tanjung (R1 and R2) and one area in Pulau (R3). A total of 19 observation plots with a size of 10 × 10 m2 were made. The water quality was further measured to identify the natural conditions affecting the outbreaks. In the present study, it was found that significant disturbance of the mangrove plants occurred due to invasions by Amphibalanus amphitrite Darwin, 1854 and Sphaeroma terebrans Spence Bate, 1866. The dangerous attack from S. terebrans has only been found at the R1 site, where we found environmental conditions such as high dissolved oxygen (DO), high total dissolved solids (TDS), and high salinity. In this area, it could affect the death of adult Avicennia alba Blume and Sonneratia alba Sm. The results obtained from this study are expected to provide preliminary data to design the best management practices in order to enhance the effectiveness of the mangrove rehabilitation strategy in the Mahakam Delta.